Characterization of the complete mitochondrial genome of the nematode-trapping fungus Drechslerella dactyloides. Issue 4 (3rd April 2023) - Zhang, Ling; Mo, Ming-He; Cao, Yan-Ru; Liang, Lian-Ming
Abstract: The complete mitochondrial genome of Drechslerella dactyloides was characterized in this study. This mitogenome is a closed circular molecule of 246860 bp in length with a GC content of 26.16%, including 87 predicted protein-coding genes, 29 transfer RNA genes, and two rRNA gens. Phylogenetic analyses based on concatenated amino acid sequences at 14 conserved mitochondrial protein-coding genes showed that D. dactyloides was closely related to Dactylellina haptotyla .